2019
DOI: 10.1038/s42003-018-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Action and mechanism of the colistin resistance enzyme MCR-4

Abstract: Colistin is the last-resort antibiotic against lethal infections with multidrug-resistant bacterial pathogens. A rainbow coalition of mobile colistin resistance (mcr) genes raises global health concerns. Here, we describe the action and mechanism of colistin resistance imparted by MCR-4, a recently-identified member from the broader MCR family. We found that MCR-4 originates from the silenced variant of Shewanella frigidimarina via progressive evolution and forms a phylogenetically-distinct group from the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 73 publications
(133 reference statements)
6
67
0
5
Order By: Relevance
“…According to the other two studies, mcr-4.3 alone did not confer phenotypic resistance to colistin (14) and showed a lack of lipid A modification function (15). Recently, a study on the action and mechanism of MCR-4 showed that revertants of mcr-4.3 (either V179G or V236F) led to its expression and conferred colistin resistance of 8 g/ml, together with the acquired function of lipid A modification (22).…”
Section: Resultsmentioning
confidence: 99%
“…According to the other two studies, mcr-4.3 alone did not confer phenotypic resistance to colistin (14) and showed a lack of lipid A modification function (15). Recently, a study on the action and mechanism of MCR-4 showed that revertants of mcr-4.3 (either V179G or V236F) led to its expression and conferred colistin resistance of 8 g/ml, together with the acquired function of lipid A modification (22).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, many species of Enterobacteriaceae are becoming increasingly resistant to colistin 2,4,6,7. One colistin resistant mechanism is the modification of Lipid A of LPS, catalyzed by the chromosome encoded machinery in Klebsiella pneumoniae , the LptA (EptA) in Neisseria , or mobile colistin resistance mcr‐1 in Enterobacteriaceae 5,8–11. Since its discovery in China, mcr‐1 resistance was reported in several other countries spanning six continents 5–7,12.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] MCR proteins function as phosphoethanolamine (PEA) transferases that catalyze the addition of a PEA moiety from phosphatidylethanolamine to the head group of lipid A through a ping-pong mechanism. 10,11 Modification of lipid A with PEA is thought to reduce the affinity of colistin to LPS, and thus confers bacterial resistance to the antibiotic. 11 To date, 10 mcr genes (mcr-1 to mcr-10) carried by plasmids with varied replicon types have been identified in various bacterial species.…”
Section: Introductionmentioning
confidence: 99%